Nivolumab exposure in a hemodialysis patient with metastatic melanoma. Issue 6 (December 2021) - Gulikers, Judith L.; Croes, Sander; Schreurs, Marco J.W.; Litjens, Elisabeth J.R.; Aarts, Maureen J.B.; van Geel, Robin M.J.M.
Abstract : The effect of intermittent hemodialysis (IHD) on nivolumab serum concentrations in patients with severe renal impairment is largely unknown. Here, we present a 79-year-old patient with metastatic melanoma and end-stage renal disease on IHD three times a week, treated with 480 mg nivolumab every 4 weeks. A serum trough concentration of nivolumab was determined before the start of the third cycle, and two samples were taken immediately before and after a hemodialysis session during this cycle. All nivolumab serum concentrations were within a similar range as those previously measured among patients without renal insufficiency, after a comparable duration of nivolumab treatment. Therefore, we conclude that IHD does not influence nivolumab exposure. Furthermore, nivolumab treatment was continued without complications and appears to be well tolerated for patients on IHD.